Math, asked by nahakswapnil311, 6 months ago

sᴏʟᴠᴇ ᴛʜɪs ᴘʟs ᴅᴏɴᴛ sᴘᴀᴍ
2ɴᴅ ᴡᴀʟᴀ​

Attachments:

Answers

Answered by muskanperween225
1

Step-by-step explanation:

It is given that (28-x) is the mean proportional of (23-x) and (19-x).

So therefore,

( {28 - x)}^{2}  = (23 - x) \times (19 - x)

 =  > ( {28)}^{2}  - 2 \times 28 \times x + ( {x)}^{2}  = 437 - 23x - 19x +  {x}^{2}

 =  > 784 - 56x +  {x}^{2}  = 437 - 42x +  {x}^{2}

 = >  {x}^{2}  -  {x}^{2}  - 56x + 42x = 437 - 784

 = >  - 14x =  - 347

 = > x =  \frac{347}{14}

The value of x is 347 / 14

Answered by Sweet318
3

Answer:

Can uhh also give me so many thanks??

Similar questions